2000
DOI: 10.1163/156856200743689
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of the polymers present in a polysulfone hollow fiber hemodialyser by covalent binding of heparin or endothelial cell surface heparan sulfate: Flow characteristics and platelet adhesion

Abstract: The present study addresses the problem of simultaneous surface modification of various polymers, i.e. polysulfone (PSU), polycarbonate (PC), and polyurethane (PU), which constitute the Ultraflux AV 600 S hollow fibre hemodialyser. An investigation was first made into six different chemical routes aimed at introducing carboxyl groups onto the surface of PSU, PC, and PU model polymers to which heparin (HE) or endothelial cell surface heparan sulfate (ESHS) was covalently bound via the reaction of residual amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…[16] Mixed C2/C3 sulfated cellulose as well as only C3 sulfated cellulose showed the lowest platelet adhesion. More pronounced is the influence of 3 positions of sulfate groups in the HE of glucosamin moiety and the 2 position of iduronic acid.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[16] Mixed C2/C3 sulfated cellulose as well as only C3 sulfated cellulose showed the lowest platelet adhesion. More pronounced is the influence of 3 positions of sulfate groups in the HE of glucosamin moiety and the 2 position of iduronic acid.…”
Section: Discussionmentioning
confidence: 90%
“…Low concentrations or no 6-O-sulfate and low concentrations of N-sulfate but high concentrations of Nacetyl groups are necessary for the most important properties of surfaces of biomaterials the platelet inertness [15] or athrombogenicity. [16] Tab. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used approach is to mimic endothelial cell layer by heparin immobilization. The beneficiary effect of heparin coatings on the membranes has been reported by many authors both in vitro [1][2][3][4][5][6][7][8][9] and in vivo [10][11][12][13][14][15]. For example, Cheung et al [1] observed that complement activation induced by hemodialysis can be modulated with heparin immobilized cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cheung et al [1] observed that complement activation induced by hemodialysis can be modulated with heparin immobilized cellulose acetate membrane. Baumann and Kokott [2] immobilized endothelial cell surface heparin sulfate (ESHS) on polysulfone (PSF), polycarbonate and polyurethane membranes and they found that the coating of these membranes by ESHS allows to generate surfaces resistant to platelet adhesion and have no effects on complement and intrinsic coagulation cascade activation. Yang and Lin [3,4] and Lin et al [5] covalently bonded chitosan/heparin conjugate onto the surface of PAN and PSF membranes and they reported improved biocompatibility of these membranes by evaluating coagulation time, plasma protein adsorption capacity and platelet adhesion [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation